2011
DOI: 10.2310/7750.2011.10032
|View full text |Cite
|
Sign up to set email alerts
|

Break Dancing: A New Risk Factor for Scarring Hair Loss

Abstract: Chronic scalp trauma due to break dancing may be a trigger for LPP. A meticulous scalp examination should be performed before making a diagnosis of nonscarring conditions of hair loss such as AGA. Early recognition of LPP and appropriate treatment are important before scarring and irreversible hair loss ensue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Dr. Jerry Shapiro and colleagues reported the case of a 26-year-old breakdancer who developed LPP localized to the scalp vertex. 8 Chronic trauma from rubbing was hypothesized to be a contributing factor in this patient. I have evaluated several patients who developed LPP following injury to the scalp from car accidents, falls, burns, neurosurgical trauma, and scalp irradiation (J. Donovan, unpublished).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Dr. Jerry Shapiro and colleagues reported the case of a 26-year-old breakdancer who developed LPP localized to the scalp vertex. 8 Chronic trauma from rubbing was hypothesized to be a contributing factor in this patient. I have evaluated several patients who developed LPP following injury to the scalp from car accidents, falls, burns, neurosurgical trauma, and scalp irradiation (J. Donovan, unpublished).…”
Section: Discussionmentioning
confidence: 88%
“…In addition to hair transplantation, other examples of skin injury have been associated with the development of LPP. Dr. Jerry Shapiro and colleagues reported the case of a 26‐year‐old breakdancer who developed LPP localized to the scalp vertex . Chronic trauma from rubbing was hypothesized to be a contributing factor in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…The Koebner phenomenon (isomorphic response) was first described in 1876 and refers to the development of cutaneous lesions at the site of tissue insult. 4 In addition, Donovan as well as Chiang and colleagues reported the development of LPP following hair transplant surgery, 8,9 raising the possibility that surgical trauma may be also be relevant to some cases of LPP. 7 Most recently, Monselise and colleagues reported a patient who developed scalp LPP following many years of repeated scalp trauma secondary to break dancing.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent research has also shown an interesting connection between traumatic skin injury and downregulation of PPAR gamma. However, the fact that his LPP developed at the exact site of his injury is intriquing and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…LPP has been described to develop after trauma (break‐dancing and motor vehicular accident) and whole brain irradiation in case reports and case series (hair transplant or facelift) . This may be induced due to the Koebner phenomenon which is present in several dermatologic diseases including lichen planus .…”
Section: Supplementmentioning
confidence: 99%